The Aesthetics of Mawlawi Poetry from the Perspective of Modern Stylistics - Abdulrahman, Dr. Lahon Qadir (Sulaimani Journal for Humanities, 2025)
Contemporary stylistics is a scientific and objective approach that explains texts through their concepts, highlighting and valuing their aesthetic qualities. This research examines the poetry of Moulawi Taokouzi using contemporary methodologies (open and integrative structuralism) and incorporates traditional rhetorical arts to interpret texts. By focusing on the text and its language as an independent structure, this study scientifically analyzes the dimensions of pleasure and beauty in his works. Key concepts such as foregrounding, parallelism, and deviation form the basis of aesthetic analysis in these texts. While traditional rhetoric is also utilized, it is combined with modern methodologies because traditional approaches alone cannot fully reveal the multiple dimensions of pleasure and beauty. Contemporary methods offer a more comprehensive and scientific means of analysis.
Keywords: Stylistics; Rhetoric; Contemporary Stylistics; Introduction; Parallelism; Deviation